2007
DOI: 10.1002/chin.200733013
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Fe‐ or Co‐Containing Carbon Nanotubes as Catalysts for NH3 Decomposition.

Abstract: Catalysts H 2000Commercial Fe-or Co-Containing Carbon Nanotubes as Catalysts for NH3 Decomposition.-Applications of commercial carbon nanotubes as catalysts for NH 3 decomposition are investigated using SEM and TEM. Carbon nanotubes containing residual Co or Fe nanoparticles are highly active for NH3 decomposition producing H2 without changing their microstructure. Co-containing carbon nanotubes exhibit superior activity to those reported for commercial catalysts. EELS reveals iron nitride as the primary activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…The negative surface charge increases with increasing pH, due to the carboxylic and phenolic groups decorating the surface even of pristine CNTs [33,56]. However, the presence of a cobalt (Co) oxide phase in BA was reported by Zhang et al [45], which has a point of zero charge at about pH 8 [58,59]. The surface-associated catalyst is thus positively charged in neutral and acidic conditions.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The negative surface charge increases with increasing pH, due to the carboxylic and phenolic groups decorating the surface even of pristine CNTs [33,56]. However, the presence of a cobalt (Co) oxide phase in BA was reported by Zhang et al [45], which has a point of zero charge at about pH 8 [58,59]. The surface-associated catalyst is thus positively charged in neutral and acidic conditions.…”
Section: Resultsmentioning
confidence: 98%
“…The comparison of the EM values associated with the surface charge of the MWCNTS supports this idea. The surface ionizations may arise from the surface acidic groups [56] and oxidized metal catalyst material [45,57]. The positive EM of BA stems from the positively charged metal oxide particles located on the surface of MWCNTS at neutral solution pH conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Transition metal catalysts also exhibit good activity for ammonia decomposition, but they usually work at higher temperatures than ruthenium-based materials. The catalytic performance of Fe-based [13][14][15][16], Co [17,18], and Ni [12,[19][20][21] catalysts for ammonia decomposition has been widely investigated over the past decades. Although Febased catalysts have lower activity and stability than commonly used Ru-and Ni-based ones, the low cost and wide availability of the former have encouraged us to develop highly efficient Fe-based catalysts [18,[22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic decomposition of ammonia over transition metals is an alternative for systems based on noble metals such as Ru, Pt, Pd, and Rh. Transition metals, Fe [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ], Ni [ 5 , 6 , 9 ], and Co [ 5 , 7 ], and also their nitrides and carbides are being intensively investigated as potential catalytic systems for the ammonia decomposition reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 6 ] found that commercial carbon nanotubes containing Co nanoparticles were highly active in the ammonia decomposition reaction. At 700 °C and under the flow of 2000 cm 3 ·g −1 ·h −1 , complete conversion of ammonia was almost reached over the carbon nanotubes based catalyst containing 4.1% of Co.…”
Section: Introductionmentioning
confidence: 99%